L-A double-stranded RNA viruslike particle replication cycle in Saccharomyces cerevisiae: particle maturation in vitro and effects of mak10 and pet18 mutations. - Fujimura, T (1987)
Previously, we found that log-phase cells of Saccharomyces cerevisiae contain a new type of viruslike particles containing only plus- strand L-A single-stranded RNA (ssRNA). These particles synthesize minus-strand RNA in an in vitro RNA polymerase reaction to produce L-A double-stranded RNA (dsRNA). The major class of particles contains L-A dsRNA and synthesizes plus-strand L-A ssRNA by a conservative mechanism. In this paper, we show that mutations in mak10 or the pet18 locus, which result in temperature-dependent replication of L-A dsRNA in vivo, also result in instability of the L-A dsRNA-containing (major class) viruslike particles in vitro. The L-A dsRNA (minus-strand)-synthesizing particles isolated by CsCl density gradient centrifugation synthesize plus-strand L-A ssRNA after completion of dsRNA (minus-strand) synthesis and have the same major coat protein as that of the major-class particles. Furthermore, the density of the dsRNA-synthesizing particles from wild-type cells shifts to that of the major-class dsRNA-containing particles as a result of the in vitro RNA polymerase reaction. Thus, L-A dsRNA-synthesizing particles undergo functional and structural maturation in vitro.